Acute hypertensive response in patients with acute intracerebral hemorrhage: A narrative review - Hawkes, Maximiliano; Rabinstein, Alejandro (Dryad, 2021)
Objective: To review the role of the acute hypertensive response in
patients with intracerebral hemorrhage, current treatment options and
areas for further research. Methods: Systematic review of the literature
to assess 1) Frequency of acute hypertensive response in intracerebral
hemorrhage 2) Consequences of acute hypertensive response in clinical
outcomes 3) Acute hypertensive response and secondary brain injury:
hematoma expansion and perihematomal edema 4) Vascular autoregulation,
safety data side effects of acute antihypertensive treatment, and 5)
Randomized clinical trials and meta-analyses. Results: An acute
hypertensive response is highly frequent in patients with acute
intracerebral hemorrhage, and it is associated with poor clinical
outcomes. However, it is not clear whether high blood pressure is a cause
poor clinical outcome, or it solely represents a marker of severity.
Although current guidelines recommend intensive blood pressure treatment
(<140 mmHg) in patients with intracerebral hemorrhage, two
randomized clinical trials have failed to demonstrate a consistent
clinical benefit from this approach, and new data suggest that intensive
blood pressure treatment could be beneficial for some patients, but
detrimental for others. Conclusions: Intracerebral hemorrhage is a
heterogenous disease, thus, a one-fit-all approach for blood pressure
treatment may be suboptimal. Further research should concentrate on
finding subgroups of patients more likely to benefit from aggressive BP
lowering, considering ICH etiology, ultraearly randomization and risk
markers of hematoma expansion on brain imaging.
Keywords: FOS: Health sciences